Development of 3D patterns for functional outdoor pants based on skin length deformation during movement - Lee, Heeran; Hong, Kyunghi; Lee, Yejin (International journal of clothing science and technology, 2017)
Purpose The seams of slim fit outdoor pants can be uncomfortable or even restrict body movement. To reduce discomfort, the authors need to determine optimal cutting lines in various designs that do not interfere with body movement. The purpose of this paper is to apply skin deformation mapping during movement to the ergonomic design of outdoor pants, focusing in particular on the 2D pattern generation of the crotch area in a 3D shape during movement. Design/methodology/approach A 3D shape and skin length deformation of the lower body were observed, including the crotch area, which is difficult to examine on the human body. To design ergonomic and streamlined outdoor pants, the authors selected seam lines where the changes in skin deformation are at their minimum based on the skin deformation mapping. In addition, the inseam along the medial thigh close to the crotch was removed to adjust the skin length of these areas, thereby increasing the extensible area of fabric necessary to adjust to a skin deformation. After selecting the seam lines, each of the 3D pattern blocks was generated by means of a 2D flattening method. In addition, the stress distribution of overlapped replica blocks along the crotch line during the 2D flattening process is a main independent factor to avoid deteriorating lower body movement as well as a good appearance. Findings Based on the results of skin deformation mapping of a human subject, this study suggested that it is best that the design line crosses where there is no skin deformation possible. And the pants were developed without the inner seam line at the upper medial thigh because of skin deformation of a large range of ±6 percent in the upper medial thigh during a 90° knee flexion or in the squatting down position. In a wear test, the developed 3D pattern without an inseam was rated higher than that with an inseam. This verified that removing the inseam, to prevent skin deformation of the medial upper thigh during knee flexion and squatting, is a logical decision. Regarding the correction of the overlapping area during arrangement of the replica, the appearance of the front of the pants was improved when 80 percent of the overlapping area was distributed near the point of the error source, which is the front of the male’s crotch line. Originality/value In this study, the crotch area, which has been difficult to observe in previous studies, were observed thoroughly and it was found that the length of the crotch curve did not increase during movement. In addition, skin deformation was mapped during a 90° knee flexion or in the squatting down position. It is expected that the overall process of developing 3D streamlined outdoor pants from 3D skin deformation mapping can be expanded to the development of patterns for other customized functional pants.